The Business Combination Process. - Dillon, Gadis J. (The Accounting Review, 1981)
Abstract ABSTRACT: In this paper, a single graphic presentation is used to identify and demonstrate the interrelationships among the alternatives and activities relevant to the business combination transaction and to post-combination operations and financial statements. Also, generalized formats for recording combination transactions are presented and discussed. Finally, the paper discusses the ways in which the instructor can use the graphic presentation to make the business combination process more understandable to students.